The messenger and the message: gp96 (GRP94)-peptide interactions in cellular immunity - Nicchitta, Christopher V. (Cell Stress Society International, 2004)
Vaccination of mice with tumor-derived stress proteins, such as Hsp70 and gp96 (GRP94), can elicit antitumor immune responses, yielding a marked suppression of tumor growth and metastasis. The molecular basis for this response is proposed to reflect a peptide-binding function for these proteins. In this view, stress proteins bind the antigenic peptide repertoire of their parent cell, and when provided to the immune system, tumor-derived stress protein– peptide complexes are processed by antigen-presenting cells (APCs) to yield the subsequent activation of tumor-directed cytotoxic T lymphocyte activity. This model predicts that stress proteins, whose primary intracellular function concerns the proper folding and assembly of nascent polypeptides, intersect with the cellular pathways responsible for the generation, processing, or assembly (or all) of peptide antigens onto nascent major histocompatability class I molecules. Recent insights into the pathways for peptide generation now allow this hypothesis to be critically examined, which is the subject of this review.